If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -2 = 2 Reorder the terms: -2 + 7y = 2 Solving -2 + 7y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 7y = 2 + 2 Combine like terms: -2 + 2 = 0 0 + 7y = 2 + 2 7y = 2 + 2 Combine like terms: 2 + 2 = 4 7y = 4 Divide each side by '7'. y = 0.5714285714 Simplifying y = 0.5714285714
| (6-3x)=(1-x)+(3-x) | | -6s=24 | | x^2-61=3 | | 10y=20 | | x/2-5=-3 | | x^2-3x-30=-8x+6 | | t-13=-28 | | (3/8)(2/7)(5/6)= | | -3(8-y)=6(y-4) | | 3(x+4)-2x= | | x^2-27x+89=-9x+8 | | x^2+3x-30=10 | | 9x^3-18x^2+x+2=0 | | e+19=-19 | | x^2-5x+7=-7x+6 | | k-5.32=1.4 | | -x+9-11x-4=41 | | x^2+4x-15=6 | | 5=3x-5 | | 32x+323*32=32 | | x^2+15x+40=x | | x=a | | 2(x+6)-x=74 | | 2m^2-2m+1=0 | | 2x+2x=7 | | 9-5x+2=4 | | y^2-15y+36=0 | | 7x+11=15x+3 | | -2x-5+8x-3=40 | | -14x-3=-5x+24 | | -7x-5=-9x-3 | | 5x^2+45x+100= |